Experimental Study of Viscous Damper Vibration Reduction Technology of Gear Shafting - Huang Xiujin; He Lidong; Xia Xueran; Liu Ming (Jixie chuandong, 2015)
According to the complex character of gearbox vibration and noise,a kind of viscous damper for controlling vibration of gear shafting system is proposed.A gearbox bench with viscous damper is built to experimentally verify the damping characteristics of the viscous dampers mounted on gear shafting.The experimental results show that the viscous damper can effectively suppress each frequency component vibration caused by the gear meshing force and the vibration at various speeds,achieving vibration amplitude reduction up to 50% with a rather wide vibration reduction frequency band.And it can get good damping effect in both radial and axial vibration.By contrasting the damping effects of the viscous damper mounted on different position,the overall damping effect is a little better for the damper installed on the shaft inside the gearbox than it installed on extended end of the shaft outside the gearbox.